E-077 Manual aspiration thrombectomy through balloon-tipped guide catheter for rapid clot burden reduction in endovascular therapy for ICA L/T occlusion. (4th July 2012) - Eesa, M; Almekhlafi, M; Mitha, A; Wong, J; Goyal, M
Abstract : Purpose: Timely recanalization during endovascular procedures for acute ischemic stroke can be challenging in cases with large clot burden as those encountered in the terminal internal carotid, T- or L-type occlusion. Methods: A novel but simple technique to achieve fast reduction in clot burden in stroke patients with occlusion of the internal carotid artery termination is described where manual suction using a 60 ml syringe applied through an 8-French Balloon guide catheter positioned in the cervical carotid vasculature with proximal flow arrest allows subsequent revascularization of the residual middle cerebral artery clot. Results: The use of manual suction through balloon-tipped guide catheter in ICA L- or T-type occlusion is illustrated. This resulted in significant reduction of the clot burden and facilitated further interventions leading to full recanalization. Conclusion: Manual suction using 60 ml syringe through balloon guide catheter is a useful and feasible technique that facilitates thrombectomy of large burden cerebral clots. Competing interests: None.